Report on the practice in industry training in fish preservation - Bermejo, Aurora A. (1960)
Fish ranks next to rice as an important staple food of our people, hence the greater concern of our government in its development in search for ways of increasing our food production. However, the perishable nature of marine products like fish is well known, especially in tropical countries like ours so that one of the most important problem which confronts us in the preservation and the utilization of our fishery products. Several standard methods, of preserving fish are practiced in the Philippines, namely; drying, canning, and refrigeration. Drying is probably the simplest method since no preservative is applied to the fish and drying is accomplished by directly exposing it in the sun. Salts preserve the fish both by dehydrating it and its own deterrent properties. Fish is also preserved with the use of crushed ice or mechanical refrigeration or a combination of both. Lowering the temperature of fish inhibits the activities of spoilage bacteria, thus preserving the fish. Canning is quite different from the above-mentioned methods of preservation ion that the process kills all the destructive agents of spoilage by heat and the fish is kept sterile in sealed containers such as cans and glass jars.